Effect of silver additions on the microstructure, mechanical properties and corrosion behavior of biodegradable Fe-30Mn-6Si. (September 2021) - Babacan, N.; Kochta, F.; Hoffmann, V.; Gemming, T.; Kühn, U.; Giebeler, L.; Gebert, A.; Hufenbach, J.
Abstract: FeMn-based alloys are promising materials for vascular implant applications, especially due to their superior mechanical properties and excellent processability. However, a further increase of the biodegradation rate of these metallic materials is desired. The addition of silver was reported to be a promising approach for accelerating the corrosion rate of those FeMn-based alloys by promoting local corrosion due to galvanic coupling, besides improving their antibacterial properties. On the other hand, the corrosion mechanisms occurring due to silver addition in various FeMn-based systems have not been understood completely. In this study, the effect of different silver contents (0.6 wt% and 1.2 wt%) on the microstructure, mechanical and corrosion properties of a cast biodegradable Fe-30Mn-6Si (wt%) is presented. By silver addition, finely distributed Ag-rich precipitates are formed in the matrix composed of austenite and ɛ-martensite, which could be detected by investigations with scanning electron and transmission electron microscopy as well as X-ray diffraction. Furthermore, an enhanced ɛ-martensite fraction was observed with rising Ag content. These changes in the microstructure significantly influence the corrosion properties. By means of potentiodynamic polarization measurements in a simulated body fluid (SBF) at 37 °C, it was revealed that the Ag additions reduce the corrosion current density, which indicates a decreased corrosion rate in comparison to Fe-30Mn-6Si. However, the alloy modifications still show higher corrosion current densities than a cast Fe-30Mn reference system. In addition, higher yield strengths for Ag-added alloys were detected by quasi-static tensile and compression tests. Data availability: The processed data required to reproduce these findings cannot be shared at this time as the data also forms part of an ongoing study. Highlights: Fe-30Mn-6Si as well as a novel Fe-30Mn-6Si-0.6Ag and Fe-30Mn-6Si-1.2Ag (wt%) alloy were produced by induction melting. Finely distributed Ag-rich precipitates as well as an enhanced ɛ-martensite fraction were observed by Ag addition. Higher yield strengths were obtained in the Ag-containing samples in tensile and compression tests. Potentiodynamic polarization tests revealed that the Ag additions reduce the corrosion current density.